2020
DOI: 10.1371/journal.pone.0226947
|View full text |Cite
|
Sign up to set email alerts
|

Early life experience and alterations of group composition shape the social grooming networks of former pet and entertainment chimpanzees (Pan troglodytes)

Abstract: The long-term effects of early life adversities on social capacities have been documented in humans and wild-caught former laboratory chimpanzees (Pan troglodytes). However, former pet and entertainment chimpanzees have received little attention to date. This study aimed to investigate the long-term effects of early life experience on 18 former pet and entertainment chimpanzees, based on social grooming data collected at a primate rescue centre over a 12year period. Moreover, we also focused on the possible sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 91 publications
2
22
0
Order By: Relevance
“…Hierarchical personality models, like Eysenck’s or the FFM, describe higher order traits which include several specific traits; and these lower traits are characterized by several behavioral responses ( Eysenck, 1990 ; DeYoung, 2006 ; DeYoung, 2010 ). Finally, it should be noted than we only had a small sample of chimpanzees, all coming from the same site (a primate rescue centre), with some of them having been exposed to traumatic past experiences which most likely shaped their personality ( Ortín et al, 2019 ) and their behavior ( Crailsheim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical personality models, like Eysenck’s or the FFM, describe higher order traits which include several specific traits; and these lower traits are characterized by several behavioral responses ( Eysenck, 1990 ; DeYoung, 2006 ; DeYoung, 2010 ). Finally, it should be noted than we only had a small sample of chimpanzees, all coming from the same site (a primate rescue centre), with some of them having been exposed to traumatic past experiences which most likely shaped their personality ( Ortín et al, 2019 ) and their behavior ( Crailsheim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our latest long-term study on grooming networks in former pet and entertainment chimpanzees demonstrated variations in the grooming activity on an individual level based on the chimpanzees’ biographical background 30 . More precisely, we found wild-caught chimpanzees as well as chimpanzees who were predominantly housed without conspecifics during infancy to be more affected in their grooming activity and their distribution of grooming compared to those who were captive born as well as those who were predominantly housed with conspecifics during infancy.…”
Section: Introductionmentioning
confidence: 94%
“…In previous studies 26 , 30 we assessed chimpanzees sociability by looking into how their atypical life history affected their grooming activities based on their individual centrality scores. In this study, however, we chose a relational approach by taking the atypical life history not only of the individual but also of his/her partner into account when investigating their directed dyadic interactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations